Analysis of Vibration Characteristics of EFT-E610P Drone Using Modal Analysis Method - Kamila, Amalia; Prattiwi, Elisabeth Anna; Setiawan, Paulus; Hartini, Dwi; Priyahapsara, Istyawan; Astuti, Yenni (Institut Teknologi Dirgantara Adisutjipto, 2025)
This research examines the vibration characteristics of the EFT-E610P type agricultural drone through flight tests and modal analysis. It aims to identify and analyze vibration properties like amplitude deviation, period, frequency, and waveform in the drone's mechanical system to ensure flight stability and safety. The study collects real-time vibration data using accelerometer sensors, processes it using Fourier transform, and interprets the main vibration features. Results show that the vibration parameters remain within a reasonable range corresponding to the drone’s natural structural properties, with no signs of instability or harmful oscillations. Amplitude fluctuations and dominant frequency shifts indicate the drone’s dynamic response to speed and structural changes but remain stable. The study concludes that the EFT-E610P drone exhibits normal vibration behavior during tests, with no negative impact on flight performance or safety, supporting its effective operation.